Marketing Research: - Easwaran, Sunanda (Oxford University Press, 2007)
Marketing Research is a comprehensive textbook specially designed to meet the needs of management students. It combines the quantitative and qualitative aspects of marketing research, and addresses its utility for both the researcher and the end-user. The text provides in-depth coverage of the key elements of the subject: its theoretical foundations, techniques of planning and design, research methodology for the implementation of quantitative and qualitative techniques, presentation and interpretation of findings through reports, and the use of marketing research techniques for developing and evaluating marketing strategies. Among the other important topics discussed are the role of research in marketing, planning for market research, types of research and sources of data, design of questionnaires and interview guides, interview techniques, methods of sampling, implementing qualitative and quantitative research, data editing and tabulation, data analysis, and computer-based techniques of data analysis. Users would find this book highly useful for its coverage of the fundamental concepts of marketing research and its relevance to business decision-making explained through classroom-tested case studies, caselets, tables, flow charts, and diagrams.